Kharif kisan sammelan 2015 sensitizes farmers - Dutt, Som (Indian Horticulture, 2019)
State level kharif kisan sammelan 2015 for horticultural crops was organized by Krishi Vigyan Kendra, Ujwa, on 17 July 2015 at village Jharoda Kalan, the epicenter of cauliflower production in Delhi. Jharoda Kalan is the adopted village of Shri Parvesh Sahib Singh, MP, under 'Sansad Adarsh Gram Yojana'. An agricultural exhibition was also organized on this occasion. The sammelan was co-sponsored by the National Horticulture Board, Gurgaon.